Efektifitas Ketepatan Triage Trauma Terhadap Aktivasi Kode Trauma Pada Pasien Trauma Kategori Merah Di Instalasi Gawat Darurat: Literature Review - Fatriani, Fatriani; Masfuri, Masfuri; Waluyo, Agung (Poltekkes Kemenkes Jakarta III, 2020)
Emergency trauma can occur at any time, occur everywhere and can be experienced by everyone. The speed and accuracy of relief in trauma emergency conditions, will determine the outcome of the assistance provided. Help for trauma patients in the Emergency Department begins when the triage officer receives the patient. The triage process sorts patients according to the patient's emergency condition using parameters of level of consciousness, respiratory status and circulation status of the patient. An efficient trauma triage system aims to assist health workers in identifying life-threatening conditions, making timely assessments and management priorities that are appropriate to the severity of the patient. Trauma Code Activation is implemented as a system for providing emergency relief in cases of trauma in the red category. In some countries the application of Trauma Team Activation in cases of trauma in the red category is the main one to optimize the initial management of trauma emergency department. Trauma Code Activation at Cipto Mangunkusumo Hospital Jakarta Emergency Department from September 2018 to June 2019 totaled 362 cases, consisting of 34.1% head injuries (7.6% bleeding), 19.3% fractures, 13% burns, 6, 7% politrauma, and there are 3.8% died.